Integrated reporting quality in Malaysia: Do chairman attributes matter? - Sumaia Ayesh Qaderi; Sitraselvi Chandren; Zaimah Abdullah (Cogent Business & Management, 2023)
In recent research, there has been increased attention on the chairman's role in companies' adoption of non-financial reporting. However, no empirical research has explored the chairman's role in improving the quality of integrated reporting (IR). Using the agency theory, this study responded to an existing research gap in the IR literature by analysing the effect of chairman attributes on IR quality. This study uses the International IR Framework (IIRF) to construct the IR index comprising 100 items and four dimensions (background, form, assurance and reliability, and content). The data consists of 363 company-year observations from Malaysian companies over the period 2017-2020. To test the developed hypotheses, panel-corrected standards error (PCSE) regression is applied. The empirical results indicate that chairmen with longer tenure and larger share ownership are adversely associated with IR quality. Nevertheless, the findings suggest that the chairman age, educational level, and financial expertise are insignificantly related to the IR quality. This is the first research, to the best of the researchers' knowledge, that investigates chairman attributes as a determinant of IR quality in Malaysia. The study's findings are important to regulators, policymakers, corporate executives, and other stakeholders interested in how the chairman's role influences companies' IR quality using evidence from an emerging Asian country-Malaysia.
Keywords: 650; Malaysia; agency theory; chairman attributes; Integrated reporting